Effectiveness of Prone Positioning in Nonintubated Intensive Care Unit Patients With Moderate to Severe Acute Respiratory Distress Syndrome by Coronavirus Disease 2019 - Taboada, Manuel (Anesth Analg, 2020)
BACKGROUND: In the treatment for severe acute respiratory distress syndrome (ARDS) from coronavirus disease 2019 (COVID-19), the World Health Organization (WHO) recommends prone positioning (PP) during mechanical ventilation for periods of 12–16 h/d to potentially improve oxygenation and survival. In this prospective observational study, we evaluated the ability of long PP sessions to improve oxygenation in awake intensive care unit (ICU) patients with moderate or severe ARDS due to COVID-19. METHODS: The study was approved by the ethics committee of Galicia (code No. 2020-188), and all patients provided informed consent. In this case series, awake patients with moderate or severe ARDS by COVID-19 admitted to the ICU at University Hospital of Santiago from March 21 to April 5, 2020 were prospectively analyzed. Patients were instructed to remain in PP as long as possible until the patient felt too tired to maintain that position. Light sedation was administered with dexmedetomidine. The following information wascollected: number and duration of PP sessions; tissue O(2) saturation (Sto(2)) and blood gases before, during, and following a PP session; need of mechanical ventilation; duration of ICU admission; and ICU outcome. Linear mixed-effects models (LMM) were fit to estimate changes from baseline with a random effect for patient. RESULTS: Seven patients with moderate or severe ARDS by COVID-19 were included. All patients received at least 1 PP session. A total of 16 PP sessions were performed in the 7 patients during the period study. The median duration of PP sessions was 10 hours. Dexmedetomidine was used in all PP sessions. Oxygenation increased in all 16sessions performed in the 7 patients. The ratio of arterial oxygen partial pressure to fractional inspired oxygen (Pao(2)/Fio(2)) significantly increased during PP (change from baseline 110 with97.5% confidence interval[CI], 19-202) and, after PP, albeit not significantly (change from baseline 38 with97.5% CI, −9.2 to 85) compared with previous supine position. Similarly, tissue oxygenation underwent a small improvement during PP (change from baseline 2.6%with 97.5% CI, 0.69-4.6) without significant changes after PP. Two patients required intubation. All patients were discharged from the ICU. CONCLUSIONS: We found that PP improved oxygenation in ICU patients with COVID-19 and moderate or severe ARDS. PP was relatively well tolerated in our patients and may be a simple strategy to improve oxygenation trying to reduce the number ofpatients in mechanical ventilation and the length of stay in the ICU, especially in COVID-19 pandemic.